An Optimization of English E-Learning at Senior High School of Purworejo - Satrio Prayogo; Juita Triana (Scripta : English Department Journal, 2020)
-This study aims to find the students’ problem during English e-learning as the base inproviding new variations for teachers in conducting e-learning. It belongs to a descriptive qualitativeresearch. The data is in the form of questionnaire answers taken from twenty students of some seniorhigh schools of Purworejo. The writers use the mean of score scale in analyzing the data. From theanalysis of data, it is found that in their e-learning, most of the students get bored since the learningprocess is monotonous, feel hard since there are too much assignment with lack of explanation, and feellost guided for the absence of a real teacher manifestation. Based on the gotten problems, the writersoffer the use of Edmodo application to provide new variation for teachers in conducting e-learningespecially in English teaching. In Edmodo, there are many complete and complex features. So it providesanother way for teachers and students to have better complement each other in e-learning. In conclusion,to solve the students’ problems in English e-learning, the teachers should be literate with the existingtechnology in the efforts of providing effective and interesting e-learning.